Some engineering aspects of the functional rehabilitation of quadriplegics - Ruch, Colin (Department of Mechanical Engineering, 2016)
Because of recent advances in medical technology, patients who have undergone severe trauma or illness are surviving where they would not have in the past. In many instances it is necessary for patients' stay in hospital to be protracted for a number of months until they are sufficiently medically fit for discharge. Many times, before such a patient can return as a productive member of society a programme of intensive rehabilitation is necessary. Amongst the most difficult tasks confronting those responsible for rehabilitating such long stay non-acute patients, is that of rehabilitating a quadriplegic. Quadriplegia, or as it is sometimes referred to, - tetraplegia - is defined as the partial or total loss of motor function in both upper and lower limbs. This thesis deals with some of the problems that are presented by patients who suffer quadriplegia, and with practical engineering solutions to some of these problems. Functional rehabilitation, by augmenting and supplementing the patient's residual ability so that he may most effectively interface with his surroundings, is the chief theme of this work. Particular emphasis is laid on the contribution of the bio-engineer to the efforts of the team of specialists assigned to rehabilitate the quadriplegic. The purpose of this project is two-fold, being directed tov1ard returning as great a degree of independence to the patient as possible, and relieving to some extent the burden placed on the family and those having to tend to the patient's needs.